Algorithm of Identification of Atypical Variants of Staphylococci, Pathogens of Chronic Pyoinflammatory Processes in Humans - L. N. Churkina; S. I. Bidnenko; M. .. Vaneechoutte; L. V. Avdeeva; A. S. Makushenko; O. B. Lutko; N. M. Oserjanskaja; N. B. Perunova (Антибиотики и Химиотерапия, 2020)
Staphylococcal pathogens of chronic relapsing infections, such as cystic pneumosclerosis and osteomyelitis are characterized by atypical morphology of the colonies (atypical variants of staphylococci) and present a subpopulation in clinically significant staphylococci. Since the loss of some phenotypic characteristics important for the genus Staphylococcus due to mutations, identification of such staphylococcal variants is difficult and sometimes impossible. An algorithm of identification of atypical variants of S.aureus (SSCVs) was developed. The advantages of the molecular methods and in particular the tRNA-PCR analysis, as well as the use of the diagnostic preparation Diastaph for correct identification of Staphylococcus atypical variants were shown.